LIFU Alleviates Neuropathic Pain by Improving the KCC2 Expression and Inhibiting the CaMKIV–KCC2 Pathway in the L4–L5 Section of the Spinal Cord. (13th April 2021) - Liao, Ye-Hui; Wang, Bin; Chen, Mo-Xian; Liu, Yao; Ao, Li-Juan
Abstract : Effective treatment remains lacking for neuropathic pain (NP), a type of intractable pain. Low-intensity focused ultrasound (LIFU), a noninvasive, cutting-edge neuromodulation technique, can effectively enhance inhibition of the central nervous system (CNS) and reduce neuronal excitability. We investigated the effect of LIFU on NP and on the expression of potassium chloride cotransporter 2 (KCC2 ) in the spinal cords of rats with peripheral nerve injury (PNI) in the lumbar 4–lumbar 5 (L4–L5) section. In this study, rats received PNI surgery on their right lower legs followed by LIFU stimulation of the L4–L5 section of the spinal cord for 4 weeks, starting 3 days after surgery. We used the 50% paw withdraw threshold (PWT50 ) to evaluate mechanical allodynia. Western blotting (WB) and immunofluorescence (IF) were used to calculate the expression of phosphorylated extracellular signal–regulated kinase 1/2 (p-ERK1/2), calcium/calmodulin-dependent protein kinase type IV (CaMKIV), phosphorylated cyclic adenosine monophosphate response element-binding protein (p-CREB), and KCC2 in the L4–L5 portion of the spinal cord after the last behavioral tests. We found that PWT50 decreased (P < 0.05 ) 3 days post-PNI surgery in the LIFU − and LIFU + groups and increased (P < 0.05 ) after 4 weeks of LIFU stimulation. The expression of p-CREB and CaMKIV decreased (P < 0.05 ) and that of KCC2 increased (P < 0.05 ) after 4 weeks of LIFU stimulation, but that of p-ERK1/2 (P > 0.05 ) was unaffected. Our study showed that LIFU could effectively alleviate NP behavior in rats with PNI by increasing the expression of KCC2 on spinal dorsal corner neurons. A possible explanation is that LIFU could inhibit the activation of the CaMKIV–KCC2 pathway.